Erosive wear of natural gas pipeline - Abdul Majid, Zulkifli; Mohsin, Rahmat; Omar, Fadhli (Penerbit UTM Press, 2008)
Erosive wear can be caused by a water jet burst from leaked water pipe laid side by side to natural gas pipeline. The erosive wear behavior of natural gas pipeline eroded by sand and water jetting was investigated. This work present the erosive wear analysis of API 5L X42, steel grade pipeline which normally used for distributing natural gas to an industrial customers by gas utility company in Malaysia. Tests were carried out by recreating above mentioned situation through the usage of 5 mm diameter orifice as the source of jetting in sand particles towards the pipe specimen that was buried at 1 meter depth. The existence of tunneling effect was established by identifying the horizontal and vertical tunneling through physical examination of the impacted surface. It was determined that the thickness of the pipe decreases with time. Determination of time taken for the pipe to rupture was established at 220 hours after continuous jetting and zero effect distance is at 450 mm from the jetting source of the relevant tests condition.